A RARE CASE OF PERIRENAL HEMATOMA AFTER URETERORENOSCOPY - B. Lazarov (Trakia Journal of Sciences)
Introduction: Ureteroscopy is a standard procedure for the treatment of ureteral stones but it carries the risk of many complications – urinary tract infections being the most common. We present a rare case of a perirenal hematoma after this procedure. Case Presentation: A male patient with bilateral ureteral stones was initially treated with stents. Later a laser disintegration of the stone in the right ureter was tried – unsuccessfully. After the procedure, a perirenal hematoma was found. Discussion: Based on our previous experience, the hematoma was completely unexpected. The ultrasound provided the initial diagnosis but it underestimated its real size -the accurate diagnosis was made with contrast-CT. The initial conservative treatment failed because of the occurrence of fever. Conclusion: Ureterorenoscopy-related hematoma is a rare, but serious complication. Its occurrence can be prevented by reducing the intrarenal pressure during the procedure and also by shortening the duration of the manipulation.